METODE KOOPERATIF TERPADU MEMBACA DAN MENULIS (CIRC) SEBAGAI METODE PENINGKATAN EFEKTIVITAS PENGAJARAN MEMBACA (READING) - Al Hakim, Luqman (UNIVERSITAS SLAMET RIYADI, 2011)
Abstract: The improvement of the effectiveness in teaching reading is necessary as a way to improve the students’ mastery of reading comprehension. Selecting the appropriate method is one way to improve the effectiveness of teaching reading. Cooperative integrated reading and composition (CIRC) is a method for teaching reading and writing by applying teammates and serving various reading activities. Dealing with it, this paper will show some important points: (1) notion of reading, (2) basic concept of CIRC, (3) purposes and benefits of teaching reading using CIRC, (4) model of teaching using CIRC, (5) the importance of CIRC in teaching reading. Keywords : cooperative integrated reading and composition (CIRC) and the effectiveness of teaching reading.